Effects of excessive screen time during online teaching on the physical and mental health of medical and dental students - Rehman, Sadia; Ali, Hasan; Sami, Zara; Sarfaraz, Raza; Ata, Madiha (Journal of the Pakistan Medical Association, 2023)
To assess the effects of excessive screen time on the health of medical and dental students due to online teaching during the Covid-19 pandemic. It was a descriptive cross-sectional study, conducted in Bahria University of Health Sciences from June 2022 to September 2022 after getting ethical approval. A total of 200 students who attended online teaching modules for at least one year through online teaching Apps, were included. A structured questionnaire was distributed using google forms. The results revealed that factors including strain on the eyes, restlessness, declined academic performance and exercise during lockdown, along with feeling connected as a group had a significant association with increased screen time. Excessive screen time has various adverse effects on the physical and mental health of medical and dental students. For improving students’ physical and mental health during online teaching we need to change teaching strategies and support the introduction of flipped classroom.